Diagnosis of pulmonary embolism in the Emergency Department - Damir Rošić; Nikola Kočet; Anđela Simić; Ingrid Prkačin; Višnja Nesek Adam (Acta Clinica Croatica, 2022)
The aim of this study was to determine the association of clinical presentation, the Wells scoring system and D-dimer values with MSCT pulmonary angiography. A case control study was conducted in the Emergency Department of the Clinical Hospital Sveti Duh throughout 2019. Patients with a referral diagnosis of a pulmonary embolism were included in the study. Patients were divided into two groups. The first group consisted of patients diagnosed with pulmonary embolism by MSCT pulmonary angiography or postmortem, and the second group consisted of patients excluded from pulmonary embolisms. For the Wells score, D-dimers, troponin, respiratory rate and peripheral blood oxygen saturation, statistically significant differences were found between groups of patients with confirmed or excluded pulmonary embolism (p <0.001). For heart rate, chest pain, syncope, and hemoptysis, no statistically significant differences were found between these two groups of patients. Deep venous thrombosis of the lower extremities was found by ultrasound in > 70% of patients with massive a pulmonary embolism. Pulmonary embolism was confirmed in all patients for whom a high risk was calculated according to the Wells score. In conclusion, a low degree of clinical probability (according to the Wells score), along with a normal concentration of D-dimer, are a sure strategy in excluding pulmonary embolism.